Identification of an RNA sponge that controls the RoxS riboregulator of central metabolism in Bacillus subtilis. Issue 11 (7th June 2021) - Durand, Sylvain; Callan-Sidat, Adam; McKeown, Josie; Li, Stephen; Kostova, Gergana; Hernandez-Fernaud, Juan R; Alam, Mohammad Tauqeer; Millard, Andrew; Allouche, Delphine; Constantinidou, Chrystala; Condon, Ciarán; Denham, Emma L
Abstract: sRNAs are a taxonomically-restricted but transcriptomically-abundant class of post-transcriptional regulators. While of major importance for adaption to the environment, we currently lack global-scale methodology enabling target identification, especially in species without known RNA hub proteins (e.g. Hfq). Using psoralen RNA cross-linking and Illumina-sequencing we identify RNA–RNA interacting pairs in vivo in Bacillus subtilis, resolving previously well-described interactants. Although sRNA–sRNA pairings are rare (compared with sRNA–mRNA), we identify a robust example involving the conserved sRNA RoxS and an unstudied sRNA RosA (Regulator of sRNA A). We show RosA to be the first confirmed RNA sponge described in a Gram-positive bacterium. RosA interacts with at least two sRNAs, RoxS and FsrA. The RosA/RoxS interaction not only affects the levels of RoxS but also its processing and regulatory activity. We also found that the transcription of RosA is repressed by CcpA, the key regulator of carbon-metabolism in B. subtilis . Since RoxS is already known to be transcriptionally controlled by malate via the transcriptional repressor Rex, its post-transcriptional regulation by CcpA via RosA places RoxS in a key position to control central metabolism in response to varying carbon sources.